(untitled) (Journal of the College of Basic Education, 2025)
Dust storms in Iraq are a recurring climatic phenomenon, caused by strong winds that lift large amounts of dust and dirt from the ground, reducing visibility and deteriorating air quality. These storms cause serious environmental and health impacts. Environmentally, dust storms contribute to soil degradation and reduced fertility, and destroy plants and crops due to dust accumulation. Health-wise, they pose a threat to people, especially those suffering from respiratory diseases such as asthma and heart disease, as they lead to an increase in cases of shortness of breath and pneumonia. In addition, dust storms can contribute to the deterioration of infrastructure by contaminating devices and equipment.